ANALISIS KEUNTUNGAN USAHA TANI AGROFORESTRY KEMIRI, COKLAT, KOPI DAN PISANG DI HUTAN KEMASYARAKATAN SESAOT, LOMBOK BARAT (Benefits analysis of agroforestry farming patterned candlenuts, cacao, coffee and banana in Sesaot community forest, West Lombok) - Ryke Nandini (Journal Penelitian Kehutanan FALOAK, 2018)
Agroforestry farming at community forest (HKm) practice provides ecological, economic and social benefits. The aimed of this study was to find the economical benefits from agroforestry with chestnut (Aleurites mollucana (L) Willd), cacao (Theobroma cacao), coffee (Coffea, sp.) and banana (Musa, sp.) pattern in HKm Sesaot. The partial economic analysis was used. Interviews were conducted on 30 HKm’s Sesaot farmers which selected purposively by grouping on three land strata (strata I: <0.25 ha, strata II: >0.25-0.45 ha, strata III: >0.45-1 ha).The data collected were farm cost and revenue from the land. The results show that agroforestry farming in HKm Sesaot provides economical benefits. Chestnut suitable to be developed in all strata, cacao in strata I and II, coffee not suitable to be developed in strata I, while banana should not be developed in all strata.